Effect of estrogen treatment on antithrombin III activity in patients with carcinoma of the prostate - Hayashi, T (Hinyokika kiyo. Acta urologica Japonica, 1989)
Since reduced antithrombin III (AT III) activity are associated with increased risk of thromboembolism, we have determined it in 39 patients with prostatic carcinoma. Pre-treatment levels were determined in 24 patients, 6 additional patients with prostatic carcinoma on estrogen treatment and 9 patients on chlormadinone acetate (CMA) therapy. In 12 of 24 patients we studied AT III levels before and after estrogen therapy was initiated. A significant decrease in AT III activity of 23.5% was found after one month on estrogen treatment, the patients on low doses of estrogen. Recovery of the levels of AT III was found after 6 months treatment even in in 5 of 6 patients who had shown depression of AT III levels initially. CMA treatment did not cause its depression. AT III levels was not connected with the stage of the disease or age of the patient